2004
DOI: 10.1590/s0004-27302004000300010
|View full text |Cite
|
Sign up to set email alerts
|

Glicemia capilar em ponta do dedo versus lóbulo de orelha: estudo comparativo dos valores resultantes e preferências dos pacientes

Abstract: To evaluate the efficacy and patient preferences of ear lobe capillary glycemia (GC) against conventional fingerstick GC, we studied 40 patients (13M/27F; 41.6 +/- 13.5 years) with type 2 diabetes mellitus (DM2). Glucose monitoring was accomplished using a digital glucometer and Accu-Chek Softclix Pro lancetator. Tests were carried out during 27 days with grade 2 of penetration (median) on the distal phalange of the right hand's third finger and on the inferior part of the right ear lobe, at the same time and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
17

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 9 publications
0
6
0
17
Order By: Relevance
“…O automonitoramento da glicose no sangue (SMBG) é uma ferramenta importantíssima no controle do diabetes 1 . A principal inconveniência do automonitoramento por meio de glicemia capilar é que os níveis de glicose são avaliados de maneira intermitente, dando apenas um quadro parcial e, portanto, incompleto das flutuações da glicose 1,2 .…”
Section: Introductionunclassified
See 2 more Smart Citations
“…O automonitoramento da glicose no sangue (SMBG) é uma ferramenta importantíssima no controle do diabetes 1 . A principal inconveniência do automonitoramento por meio de glicemia capilar é que os níveis de glicose são avaliados de maneira intermitente, dando apenas um quadro parcial e, portanto, incompleto das flutuações da glicose 1,2 .…”
Section: Introductionunclassified
“…A principal inconveniência do automonitoramento por meio de glicemia capilar é que os níveis de glicose são avaliados de maneira intermitente, dando apenas um quadro parcial e, portanto, incompleto das flutuações da glicose 1,2 . Devido a muitos fatores, inclusive dor e inconveniência, muitas crianças com diabetes não aceitam as freqüentes picadas na ponta do dedo necessárias nesse tipo de procedimento.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…1 The major inconvenience of SMBG is due to the fact that blood glucose is only intermittently measured by fingerstick capillary blood sampling, from which only a partial and therefore incomplete picture of blood glucose fluctuations can be made. 1,2 Because of many factors, including pain and inconvenience, many children with diabetes do not accept frequent fingersticks for SMBG. One parent of a child with diabetes compared his daughters daily four SMBG values to hearing four notes of a symphony.…”
mentioning
confidence: 99%
“…3 The availability of the continuous glucose monitoring system (CGMS) (Medtronic; Northridge, CA, USA) offers the opportunity for pediatric type 1 diabetic patients to match the demands of intensive therapy with the intensive monitoring of blood glucose levels. 1,2 The diabetes control and complications trial (DCCT) established that intensive and multidisciplinary treatment of type 1 diabetes mellitus (DM1) improves metabolic control and reduces the complications of the disease. 4 Estimates showed that a significant damage to quality of life is frequently due to DM1 in children and adolescents, including functional limitations, social and economic stress, even major depression.…”
mentioning
confidence: 99%